Influencer Effect during Coronavirus Period within the_x000D_ Framework of the Consumption Society - YEL, ALİ MURAT (My University, 2021)
Consumption culture is discussed by many theorists. Since most of societies arebased on consumption, they started to be known as consumption society. Capitalist socialunderstanding based on production in early days has become consumption-based in time andhas shown itself in all areas of life. With emergence of social media networks invented witheffects of technological developments, phenomenon of consumption has been transferred to anew platform. Using influencers, which most companies have a large number of followers formarketing and product promotion, is an indicator of prevalence of consumption. In lastmonth of 2019, due to deadly Covid-19 virus, which emerged in Wuhan, China and spreadto the world, people chose to stay from their homes and prefer online shopping to avoidinfection. Therefore, in this study, effect of influencers on shopping habits of the society duringCovid-19 virus period was discussed based on phenomenon of consumer society.

Tüketim kültürü pek çok teorisyen tarafından tartışılmaktadır. Toplumların çoğu_x000D_ tüketimi temel aldıkları için tüketim toplumu olarak anılmaya başlamışlardır. İlk zamanlar_x000D_ üretimi temel alan kapitalist toplumsal anlayış zaman içerisinde tüketim temelli hale gelmiş_x000D_ olup yaşamın her alanında kendisini açıkça göstermiştir. Teknolojik gelişmelerin etkileri ile_x000D_ icat edilen sosyal medya ağlarının ortaya çıkışıyla tüketim olgusu yeni bir platforma_x000D_ taşınmıştır. Şirketlerin çoğu pazarlama ve ürün tanıtımı için çok sayıda takipçileri olan_x000D_ influencer kullanımı, tüketimin yaygınlığının bir göstergesi niteliğindedir. 2019 yılının son_x000D_ ayında Çin’in Vuhan kentinde ortaya çıkıp dünyaya yayılan öldürücü Covid-19 virüsü_x000D_ yüzünden insanlar virüsün bulaşmasından kurtulmak için evlerinde kalarak çevrimiçi_x000D_ alışverişi tercih etmişlerdir. Bu bağlamda bu çalışmada tüketim toplumu olgusu temel_x000D_ alınarak Covid-19 virüsü döneminde Influencerların toplumun alışveriş alışkanlıklarına_x000D_ olan etkisi ele alınmıştır.
Tüketim Toplumu Kavramı Çerçevesinde Koronavirüs Döneminde Influencer Etkisi